Adhesion formation of the parietal and visceral peritoneum: an explanation for the controversy on the use of autologous and alloplastic barriers? - Wallwiener, Diethelm; Meyer, Anke; Bastert, Gunther (Fertility and sterility, 1998)
Objective: To compare formation of adhesions after injury to both parietal and visceral peritoneum and to determine the benefit of autologous transplants and alloplastic barriers in adhesion prevention. Design: Experimental prospective animal study and prospective randomized clinical study. Setting: An academic research environment. Patient(s): Forty women undergoing laparoscopy for endometriosis treatment. Intervention(s): In 60 rats, either the visceral or parietal peritoneum was injured and covered with autologous peritoneal transplants in half of the animals. The formation of adhesions was assessed 21 days postoperatively. In women, adhesions were evaluated 3 months after surgery with or without placement of alloplastic barriers on visceral lesions. Main Outcome Measure(s): Adhesions evaluated according to a scoring system. Result(s): Adhesions after injury of the visceral peritoneum in rats were significantly more severe than those from the parietal peritoneum. Autologous peritoneal transplants led to fewer adhesions especially after serosal injuries. Female volunteers treated with alloplastic barrier material showed less severe adhesions than the control group. Conclusion(s): The present data indicate that the potential to form adhesions is significantly higher in visceral than in parietal peritoneal lesions. The development of adhesions after injury to the visceral peritoneum could be reduced by a synthetic barrier material.